Структура центрів матричного свічення у бездомішкових і легованих іонами РЗЕ кристалах вольфрамату свинцю типу шееліту - Chukova, O.; Nedilko, S. (Publishing house "Academperiodika", 2019)
The paper reports the investigation of a structure of luminescence spectra of PbWO4 (PWO) crystals. The doping of the samples with rare earth (RE) impurities is used in order to obtain more information about the composition of spectra of the PWO matrix emission and the structure of its luminescence centers. The decomposition of the emission spectra onto individual bands has shown that 5 bands contribute to the total spectra of all the undoped and RE-doped samples at 10 K. The maxima of the obtained bands are 1.95, 2.2, 2.45, 2.7, and 3.0 eV. Effects of the RE-doping and the annealing on relative intensities of these bands are considered. The nature of luminescence and the structure of the centers involved in the excitation and emission processes responsible for each of the separated bands are discussed.